SISTEM INFORMASI PEMBAYARAN SEKOLAH DENGAN MEMANFAATKAN TEKNOLOGI BARCODE BERBASIS MULTIUSER DI SMP MUHAMMADIYAH 3 SEMARANG - Bagus Panuntun; Arsito Ari Kuncoro (Universitas Sains dan Teknologi Komputer, 2019)
Along with the development of information technology that is increasingly rapid, the use of information technology at this time is an important requirement in every agency or company An educational institution requires good administrative management with the aim to improve services to students, the school payment system in the form of Education Provision Contribution (SPP) and Donation of Institutional Development (SPI) at SMP Muhammadiyah 3 Semarang is still done conventionally, where the recording of data and the payment process of SPP and SPI are written into diaries, ledgers and spreadsheet applications which results in the accumulation of data in the form of archives. In the data collection of students and the payment process takes a relatively long time, so that during the payment process results in long queues in the administration and requires a long time to make payment reports and arrears SPP and SPI which are needed quickly.Developments in the field of science and technology were developed with the aim of solving problems and making it easier for users to complete work tasks. The use of barcode technology is one of the technologies that can respond to the provision of fast, accurate and accurate information. Barcode technology is applied to student cards that function as student IDs and also as student payment cards